Odpowiedzi

2009-12-20T18:31:01+01:00
-4x + 2x - 6x + x - 3x= -10x
½ xy + 0,5xy - xy +3xy= 3xy
x²a - 2x²a + 0,4x²a= -0,6x²a
x + 2y - x - 2y + 3y - x= -x+3y
4x + 3x² - 2 - 4x + x² + 1= 4x²-1
a + 1 - a² +2a + a² - 3= 3a-2
5 - 2x + x - 6 + 3x - 1 + ½x + 0,5= 2,5x-2
Najlepsza Odpowiedź!
2009-12-20T18:32:24+01:00
-4x + 2x - 6x + x - 3x=-10x
½ xy + 0,5xy - xy +3xy=3xy
x²a - 2x²a + 0,4x²a=-0,6x²a
x + 2y - x - 2y + 3y - x=3y-x
4x + 3x² - 2 - 4x + x² + 1=4x²-1
a + 1 - a² +2a + a² - 3=3a-2
5 - 2x + x - 6 + 3x - 1 + ½x + 0,5=-1,5+2½x
2009-12-20T18:33:18+01:00
-4x + 2x - 6x + x - 3x= -10x
½ xy + 0,5xy - xy +3xy= 3xy
x²a - 2x²a + 0,4x²a=0,6x²a
x + 2y - x - 2y + 3y - x= -x + 3y
4x + 3x² - 2 - 4x + x² + 1= 4x² - 1
a + 1 - a² +2a + a² - 3= 3a - 2
5 - 2x + x - 6 + 3x - 1 + ½x + 0,5= -1,5 + 2,5x